Malnutrition among Malaysian Adolescents: Findings from National Health and Morbidity Survey (NHMS) 2011. - Azli Baharudin; Ahmad Ali Zainuddin; Rusidah Selamat; Suhaila Abdul Ghaffar; Khor, Geok Lin; Poh, Bee Koon; Norimah Abd Karim; Kee, Chee Cheong; Ng, Chee Kai; Noor Ani Ahmad; Syafinaz Mohd Sallehuddin; Tahir Aris (Universiti Kebangsaan Malaysia, 2013)
Malnutrition can be associated as one of the factors which affect health status. The term is used to describe imbalance of nutrients either over- or under-nourished, resulting in measurable adverse effects on body composition, function and clinical outcome.